Compound heterozygous variants of the SLC26A4 gene in a Chinese family with enlarged vestibular aqueducts - Xiaohui He; Shaozhi Zhao; Lin Shi; Yitong Lu; Yintong Yang; Xinwen Zhang (BMC, 2022)
Abstract Background To investigate the genetic causes of hearing loss in patients with enlarged vestibular aqueduct (EVA), the SLC26A4-related genotypes and phenotypes were analyzed. SLC26A4 gene is closely associated with EVA and its homozygous mutations or compound heterozygous mutations may cause deafness and strongly affect quality of life. Methods The patients who came to our hospital for hearing test and accompanied by bilateral hearing abnormalities were collected for fifteen deafness-related gene mutations detection. Those who are positive will be verified by Sanger sequencing, combined with family history, hearing test, and computerized tomography (CT) of the temporal bone, aiming to diagnose the enlarged vestibular aqueducts. Whole-exome sequencing were performed when necessary. Results Our patient failed hearing screening on both sides twice, and EVA (> 1.5 mm) was diagnosed by CT. This study has identified a novel missense mutation in the SLC26A4 gene, c.2069T>A, which in compound heterozygosity with c.1174A>T is likely to be the cause of hearing loss. The novel heterozygous c.2069T>A mutation of SLC26A4 gene has been submitted to Clinvar with Variation ID 1,048,780. Conclusion Our findings expand the gene mutation spectrum of SLC26A4 and provide additional knowledge for diagnosis and genetic counseling associated with EVA-induced hearing loss.